Hemoglobins of African origin in quilombola communities of Tocantins State, Brazil - Teles, Annyelle Figueredo (2019)
OBJECTIVE: To verify the incidence of hemoglobins of African descent (HbS and HbC) in quilombola communities in Tocantins State, Brazil. MATERIALS AND METHODS: Blood samples were collected from 14 quilombola communities in the State; the screening was performed in cellulose acetate electrophoresis (pH 8.6), and those samples with altered standard were submitted to high performance liquid chromatography, recording gender and age of the quilombola people. RESULTS: The analysis of the results showed that of the 822 quilombolas investigated 95 presented abnormal hemoglobins, 0.5% with sickle cell disease (HbSS); 5.7% for hemoglobin S trait (HbAS); 4.9% for hemoglobin C trait (HbAC); 0.2% with increased fetal hemoglobin; 0.1% with increased hemoglobin A2; and 88.4% with normal hemoglobin (HbAA). HbSS was observed in infant and adolescent groups and HbAS and HbAC in all age groups. About sex, it was not possible to suggest the maternal effect for HbS due to the greater quantitative of males with this genetic information. CONCLUSION: In the current study the incidence of HbS and HbC observed in quilombola communities was within the expected range for the Northern Region of Brazil. However, the high prevalence of sickle cell disease and the high frequency of sickle cell trait were highlighted in some quilombola communities with special attention to the southern region of the State. Thus, the results presented in this study indicate an imminent risk for the increased incidence of that disease in Tocantins.